United Nations Security Council’s extrajudicial measures and responsibility towards fundamental human rights - Javad Safdari,; Zamani, Seyyed Qasem (International Journal of Psychosocial Rehabilitation, 2020)
The Security Council of the United Nations, after the end of the Cold War and especially since the 1990s, has expanded its activities in many other areas, such as support for human rights and related obligations, through transforming the traditional concept of peacekeeping and security making in accordance with paragraphs one and two of Article 24 of the UN Charter. The main challenge has been with the Security Councilmeasures and decisions with reference to Chapter Seven and the unlawfulness and incompatibility of some of its decisions and measures with the Charter and human rights obligations as well as international law and human rights judicial procedures. The present paper studies the difficulties related to the admission of the Security Council as an extrajudicial institute and compliance with its international obligations and responsibilities towards grave human rights violations concerning Chapter Seven and humanitarian interventions. The findings suggest that despite the efforts of the council to support human rights and its mechanisms, there seems to be a clear violation its managerial performance and treatment. In other words, some of the Security Council decisions and measures have failed to prevent human rights violations and in fact resulted in more breaches and inefficiency of the council. Researchers recommend reforms in some the council’s procedures and behavioral patterns through imposing regular supervisory mechanisms.